STUDI PERBANDINGAN TINGKAT PELAYANAN KORIDOR JALAN UTAMA KAWASAN SUMMARECON TERHADAP PERKIRAAN TINGKAT PELAYANAN JALAN IR. H. JUANDA DAN JALAN PERJUANGAN BEKASI BERDASARKAN VOLUME THROUGH TRAFFIC EKSISTING KAWASAN - Rizaldy Mahardhika, Muhammad
Bekasi City as part of the Metropolitan Jabodetabek has a population that continues to increase, about 2.45 million people with a growth of 1.3 percent. The increase in population results in an increase in the number of movements, which means that there is an increase in demand for road needs. In 2010, PT Summarecon built a residential area with other facilities such as a main public road corridor, which created a new alternative to the movement previously accommodated by Ir. H. Juanda Road and Perjuangan Road. Therefore, to find out the benefits of having the main Summarecon road, it is necessary to compare the service level of the main road corridor in the Summarecon area to the estimated service level of Ir. H. Juanda Road and Perjuangan Road based on the volume through traffic of the existing Summarecon area, the results can be used for future conditions whether the involvement of the private sector in road infrastructure development will benefit the surrounding roads. This can be achieved by calculating the existing service level of the main road in the Summarecon Bekasi area, calculating the volume of generation, attraction, and through traffic of the main road in the Summarecon Bekasi area, and calculating the estimated service level of Ir. H. Juanda Road and Perjuangan Road based on the volume through traffic of the existing Summarecon area. The way to get this calculation is through traffic counting at the two doors of the Summarecon Bekasi area, which is then processed by converting the number of vehicles into passenger car units. After that, the generation and attraction volumes are calculated, as well as the traffic through which is then used to find the service level based on the capacity of the main roads in the Summarecon Bekasi area and Ir. H. Juanda Road and Perjuangan Road. Based on the analysis conducted, it was found that the main road corridor in the Summarecon area has a better service level than Ir. H. Juanda Road and Perjuangan Road. Therefore, recommendations were made to increase the capacity of Ir. H. Juanda Road and Perjuangan Road of Bekasi as an initiative of the Bekasi City Government. In addition, there is also a need for cooperation between the local government and the private sector to build infrastructure such as roads or flyovers, so that local governments must embrace third parties in developing mutually beneficial developments, as well as for the people who move through these roads.